Trajectory optimization of an innovative-turbofan-powered aircraft based on particle swarm approach for low environmental impact. Issue 1 (1st January 2019) - Colmenares-Quintero, Ramón Fernando; Góez-Sánchez, Germán David; Colmenares-Quintero, Juan Carlos
Abstract: Flight route planning in civil aviation seeks to minimize the total cost of the operation while maintaining high safety standards. Therefore, the increase in the number of air routes as well as air traffic in commercial aviation poses new challenges for planning optimal routes. This work proposes a method to plan routes using a bio-inspired technique called Particle Swarm Optimization (PSO). Such method aims to obtain the shortest distance between two points, thus reducing NOX, CO2 and H2 O emissions. The analysis of fuel consumption and emissions was carried out using a multidisciplinary simulation tool, the Preliminary Multidisciplinary Design Framework (PMDF). The latter was applied to an aircraft with a conventional configuration powered by an innovative turbofan engine. The planner provides a new route with the shortest possible flight distance and, at the same time, considers unexpected obstacles on the route, thus minimizing fuel consumption and possible polluting emissions into the atmosphere. This is one of a series of works that will use the proposed design tool. Different economic and environmental scenarios will be evaluated once such studies are concluded.